Foxp3+ CD4+ regulatory T cells control dendritic cells in inducing antigen-specific immunity to emerging SARS-CoV-2 antigens - Uraki, Ryuta; Imai, Masaki; Ito, Mutsumi; Shime, Hiroaki; Odanaka, Mizuyu; Okuda, Moe; Kawaoka, Yoshihiro; Yamazaki, Sayuri (PLoS pathogens, 2021)
Regulatory T (Treg) cells, which constitute about 5–10% of CD4 + T cells expressing Foxp3 transcription factor and CD25(IL-2 receptor α chain), are key regulators in controlling immunological self-tolerance and various immune responses. However, how Treg cells control antigen-specific immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains unclear. In this study, we examined the effect of transient breakdown of the immunological tolerance induced by Treg-cell depletion on adaptive immune responses against administered SARS-CoV-2 antigen, spike protein 1 (S1). Notably, without the use of adjuvants, transient Treg-cell depletion in mice induced anti-S1 antibodies that neutralized authentic SARS-CoV-2, follicular helper T cell formation and S1-binding germinal center B cell responses, but prevented the onset of developing autoimmune diseases. To further clarify the mechanisms, we investigated maturation of dendritic cells (DCs), which is essential to initiate antigen-specific immunity. We found that the transient Treg-cell depletion resulted in maturation of both migratory and resident DCs in draining lymph nodes that captured S1-antigen. Moreover, we observed S1-specific CD4 + T cells and CD8 + T cells with interferon-γ production. Thus, captured S1 was successfully presented by DCs, including cross-presentation to CD8 + T cells. These data indicate that transient Treg-cell depletion in the absence of adjuvants induces maturation of antigen-presenting DCs and succeeds in generating antigen-specific humoral and cellular immunity against emerging SARS-CoV-2 antigens. Finally, we showed that SARS-CoV-2 antigen-specific immune responses induced by transient Treg-cell depletion in the absence of adjuvants were compatible with those induced with an effective adjuvant, polyriboinosinic:polyribocytidyl acid (poly IC) and that the combination of transient Treg-cell depletion with poly IC induced potent responses. These findings highlight the capacity for manipulating Treg cells to induce protective adaptive immunity to SARS-CoV-2 with activating antigen-presenting DCs, which may improve the efficacy of ongoing vaccine therapies and help enhance responses to emerging SARS-CoV-2 variants.